I4U submission to NIST SRE 2012: A large-scale collaborative effort for noise-robust speaker verification - Saeidi, R.; Lee, K.A.; Kinnunen, T.; Hasan, T.; Fauve, B.; Bousquet, P.M.; Khoury, E.; Martinez, P.L.S.; Kua, J.M.K.; You, C.H.; Sun, H.; Larcher, A.; et al. (My University, 2013)
I4U is a joint entry of nine research Institutes and Universities across 4 continents to NIST SRE 2012. It started with a brief discussion during the Odyssey 2012 workshop in Singapore. An online discussion group was soon set up, providing a dis¬cussion platform for different issues surrounding NIST SRE' 12. Noisy test segments, uneven multi-session training, variable en¬rollment duration, and the issue of open-set identification were actively discussed leading to various solutions integrated to the I4U submission. The joint submission and several of its 17 sub¬systems were among top-performing systems. We summarize the lessons learnt from this large-scale effort.
Keywords: Speaker Verification; NIST SRE 2012